Olga Kovalets’. Oleksandr Konys’ky – the life dedicated to Ukraine - Kovalets’, Olga (Young Scholars Grinchenko – Seton International Journal, 2021)
Abstract. The article is devoted to the personality of Oleksandr Konys’ky (1836–1900), a Ukrainian public figure, enlightener, writer, pedagogue, translator, publisher, lexicographer, professional lawyer, journalist, author of the words of the spiritual hymn “Prayer for Ukraine”, the translator of the Taras Shevchenko Diary, the founder of Shevchenko studies, a bright personality in the Ukrainian social, political and literary process of the second half of the 19th century. The relevance of the article consists in researching his life and multifaceted activities. Oleksandr Konys’ky defended the interests of Ukrainianness and Ukrainians throughout all his life. He did not compromise in the national cause. He awakened the indifferents by his writings and words. He burned with love for Ukraine and ignited with this fire the hearts of many of his spiritual followers. Behind this fire of love were his real deeds, his foresight and talent to see the future, his belief and conviction that Ukraine would gain independence. His greatest work, the spiritual hymn “Prayer for Ukraine”, he wrote in 1885, 135 years ago. Oleksandr Konys’ky sincerely believed that with the words of his prayer: “Lord, oh the Great and Almighty, / Protect our beloved Ukraine, / Bless her with freedom and light / Of your holy rays. / With learning and knowledge enlighten / Us, your children small, / In love pure and everlasting / Let us, oh Lord, grow. / We pray, oh Lord Almighty, / Protect our beloved Ukraine, / Grant our people and country / All your kindness and grace. / Bless us with freedom, bless us with wisdom, / Guide into kind world, / Bless us, oh Lord, with good fortune / For ever and evermore”, – will grow the future Ukrainians of the future Ukrainian independent state. Educator-enlightener Oleksandr Konys’ky considered his goal to form the national consciousness and self-consciousness of the Ukrainian people through enlightenment, education, dissemination of knowledge, literacy of children and adults. He had many ideas, was optimistic, showed energy and great activity in public life. Oleksandr Konys’ky was a key figure in the national liberation movement of the second half of the 19th century. Oleksandr Konis’ky was the creator of the ideological mental image of the modern Ukrainian. He was the first independent of the Ukrainian hromadivsʹkyy movement. He became the organizer of the national Ukrainian science and put a dividing line between the Russian and Ukrainian science. Oleksandr Konys’ky was the first truly Ukrainian conciliar, he stood at the cradle of the formation of all-Ukrainian culture in Galicia: a united literary language, a common fiction, a single national science, synchronized socio-political activities in the international arena. Keywords: Olexandr Konys’ky, Ukrainianness, enlightener, national consciousness, education, enlightenment, independence, conciliarism, national liberation movement, founder of Shevchenko studies, second half of the 19th century, Kyiv.